Small molecule-based fluorescent probes as tool compounds for chemokine receptors CXCR4 and ACKR3 - Dekkers, Sebastian (2019)
Chemokine receptors CXCR4 and ACKR3 form, together with their shared ligand CXCL12, a highly intricate signalling axis that recently has emerged as a promising target for the treatment of cancer. To further the understanding of how these receptors function, and how they are involved in the various processes of tumour development and metastasis, efforts were made to develop fluorescent tool compounds. In this thesis is described the design, synthesis, and biological characterisation of small molecule-based fluorescent probes for CXCR4 and ACKR3. It examines the use of these fluorescent probes as toolkit compounds for the study of ligand-receptor interactions and the characterisation of novel ligands. It furthermore shows their application in live cell microscopy. A thorough evaluation of SAR of reported small molecule CXCR4 receptor inhibitors, in combination with in silico design, informed the synthetic strategy for linker and fluorophore conjugation. This project explored three chemical classes of CXCR4 receptor inhibitors, leading to the development of multiple high affinity probes that show specific binding in a novel fluorescence-based NanoBRETTM binding assay (pKd values ranging 6.6-7.1). Using the same NanoBRETTM approach their utility in competition binding experiments was assessed, where they showed to be fully displaceable by established small molecule inhibitors. Additionally, the ability of these fluorescent probes to affect CXCL12-mediated signalling of CXCR4 was assessed in a functional GloSensor™ cAMP assay. Here, the antagonist nature of the small molecules these probes were based on was found to be retained in the final probes. Finally, live cell confocal microscopy using selected compounds (6,6-dimethyl-5,6-dihydroimidazo[2,1-b]thiazol-3-yl)methyl(E)-N-cyclohexyl-N'-((1r,4r)-4-(6-(2-(4-((E)-2-(5,5-difluoro-7-(thiophen-2-yl)-5H-4λ4,5λ4-dipyrrolo[1,2-c:2',1'f][1,3,2]diazaborinin-3-yl)vinyl)phenoxy)acetamido)hexanamido)cyclo-hexyl)carbamimidothioate (9), (S,E)-6-(2-(4-(2-(5,5-difluoro-7-(thiophen-2-yl)-5H-4λ4,5λ4-dipyrrolo[1,2-c:2',1'-f][1,3,2]diazaborinin-3-yl)vinyl)phenoxy)acetamido)-N-(3-(3-((methyl(5,6,7,8-tetrahydroquinolin-8-yl)amino)methyl)isoquinolin-4-yl)propyl)hexanamide (22), and (S,E)-N-(4-(((1H-benzo[d]imidazol-2-yl)methyl)(5,6,7,8-tetrahydroquinolin-8-yl)amino)butyl)-6-(2-(4-(2-(5,5-difluoro-7-(thiophen-2-yl)-5H-4λ4,5λ4-dipyrrolo[1,2-c:2',1'-f][1,3,2]diazaborinin-3-yl)vinyl)phenoxy)acetamido)hexanamide (30) showed clear localisation of the fluorescent ligands on the cell membrane, localising neatly at sites of high receptor expression. Utilizing a similar approach high affinity fluorescent probes were developed for the atypical chemokine receptor ACKR3. An homology model of ACKR3 bound to small molecule agonist GD301 provided rational for the structural modification of this ligand and the incorporation of BODIPY dyes. A series of fluorescent derivatives were synthesised and assessed in a NanoBRETTM binding assay on whole cells. Nine fluorescent ligands were developed, of which six showed good affinity towards the receptor (pKd values ranging 6.1-7.1). Competition binding experiments using the same NanoBRETTM approach revealed these fluorescent conjugates interact with the receptor in a competitive manner, and suggests these probes are viable toolkit compounds in the characterisation of small molecule ligands. Finally, live cell confocal imaging with selected probe (R,E)-3-(2-(6-(3-(5,5-difluoro-7,9-dimethyl-5H-4λ4,5λ4-dipyrrolo[1,2-c:2',1'-f][1,3,2]diazaborinin-2-yl)propanamido)hexanamido)ethoxy)-N-(3-(2-fluorophenyl)-2-methylallyl)-4,5-dimethoxy-N-(2-(1-methylpyrrolidin-2-yl)ethyl)benzamide (40a) showed good localisation of the probe on the cell membrane. Upon binding to the receptor, the probe was furthermore able to induce internalisation over time, suggesting an agonist-like response. Treatment with a high concentration of competitive ligand resulted in complete dissipation of the fluorescent signal of the probe, revealing very low levels of nonspecific binding. Overall, this project has led to the successful development of fluorescent probes for the chemokine receptors CXCR4 and ACKR3. With their high affinity for the receptor, alongside their excellent fluorescent properties, these compounds provide valuable means to study these receptors in vitro, and facilitate live imaging techniques such as confocal microscopy and flow cytometry.